SOCIAL-PHILOSOPHICAL ANALYSIS OF SOCIAL LIFE AND GLOBALIZATION PROCESSES (Modern education and development, 2025)
This article analyzes the processes of social life and globalization, the role of information in the globalization of the economy, the introduction and rapid development of information and communication and computer technologies, their significant changes in our society, the formation of a global information society, and the rapid and high-quality circulation of information, which has become the main criterion for the development and prosperity of a country.